Unlocking the catalytic activities of 2H-phase Mo-based compounds via topological conversion reaction. (December 2021) - Du, Zhiguo; Wang, Shuai; Hu, Riming; Zhang, Di; Gu, Jianan; Chen, Xiao; Shang, Jiaxiang; Li, Bin; Yang, Shubin; Guo, Lin
Graphical abstract: The catalytic activities of 2H phase molybdenum-based compounds are unlocked via topological conversion reaction from Mo2 GeC MAX phase to accordion-like molybdenum phosphosulphide. During the conversion reaction, phosphorus atoms can be implanted into the sandwich-like S-Mo-S planes and gradually substitute sulfur atoms, which are beneficial to optimize the electronic configuration and facilitate to absorb water molecules, unlocking the inert basal planes of 2H phase molybdenum-based compounds. The accordion-like molybdenum phosphosulphide exhibits high hydrogen production rates up to 288 mmol g −1  h −1  cm −2 at a high loading of 3 mg cm −2 and ultralong durability up to 35, 000 cycles. Abstract: Although 2H molybdenum disulfide (MoS2 ) layers are highly desirable for hydrogen evolution reaction (HER) owing to their high chemical stabilities and low cost, the inert basal plane and semiconducting nature severely hinder their practical applications. Here, the catalytic activities of 2H phase molybdenum-based compounds are unlocked via topological conversion reaction from Mo2 GeC MAX phase to accordion-like molybdenum phosphosulphide. During the conversion reaction, phosphorus atoms can be implanted into the sandwich-like S-Mo-S planes and gradually substitute sulfur atoms, which are beneficial to optimize the electronic configuration and facilitate to absorb water molecules, unlocking the inert basal planes of 2H phase molybdenum-based compounds. The accordion-like molybdenum phosphosulphide exhibits high hydrogen production rates up to 288 mmol g −1  h −1  cm −2 at a high loading of 3 mg cm −2 and ultralong durability up to 35, 000 cycles, satisfying the practical application for HER.